Costs of cervical disc replacement versus anterior cervical discectomy and fusion for treatment of single-level cervical disc disease: an analysis of the Blue Health Intelligence database for acute and long-term costs and complications - Radcliff, Kris; Zigler, Jeff; Zigler, Jack (Spine (Philadelphia, Pa. 1976), 2015)
Retrospective review of prospectively collective administrative data. The purpose of this study was to determine the reoperation rates, adverse event rate, as well as the direct and follow-on costs of cervical disc arthroplasty (CDA) compared with anterior cervical discectomy and fusion (ACDF) in a "real-world" population of patients with single-level symptomatic cervical disc disease. Until very recently, there was a paucity of human clinical data to demonstrate that CDA lowers the rate of adjacent segment disease over ACDF. This was a retrospective, matched cohort analysis of a prospectively collected database of costs and outcomes for patients aged 18 to 60 years, who were continuously enrolled in a Blue Cross Plan contributing data to a claims database. Inclusion criteria were as follows: all patients who were treated surgically with either CDA or ACDF between January 2008 and December 2009, with single-level cervical pathology and claims reflecting at least 6 weeks of nonsurgical preoperative care without claims history of prior surgery. There were 6635 ACDF patients and 327 CDA patients. There were no significant differences in the incidence of comorbidities or mean follow-up time (ACDF 25.7 mo vs. CDA 26.1 mo) between groups. By 36 months postoperatively, the reoperation rate was significantly increased in the ACDF group (10.5%) versus the CDA group (5.7%) (hazard ratio, P = 0.0214). The index surgery and 90-day global window costs were significantly lower in the CDA groups. At final follow-up, there was a statistically significant reduction in total costs paid by insurer in CDA patients (CDA $34,979 vs. ACDF $39,820). Patients who underwent CDA for single-level degenerative disease had lower readmission rates, lower reoperation rates, and reduced index and total costs than those treated with ACDF. CDA was effective in reducing the monthly cost of care compared with ACDF. 2.